An overview of structurally-controlled dolostone-limestone transitions in the stratigraphic record - Koeshidayatullah, Ardiansyah; Corlett, Hilary; Hollis, Cathy (My University, 2021)
In structurally-controlled dolomitization systems, there is a general consensus that the formation of dolostone-limestone transitions, termed here as “dolomitization fronts”, is governed by either the presence of an ultra-low permeability zone (fluid barrier) or changes in dolomitization potential and kinetics. However, the actual processes controlling the abrupt termination of dolostone bodies, and their corresponding morphology and dimension, are still relatively poorly understood. To address these challenges, we aim to (i) review the different origin and styles of structurally-controlled dolomitization fronts in the stratigraphic record and (ii) provide a standardized framework and quantitative insight to describe and interpret dolomitization fronts. To achieve this, field observations across geologic timescales and geodynamic settings are complimented with published data to document different styles of structurally-controlled dolomitization fronts. The results show that the following morphologies are associated with both tabular and columnar dolostone bodies: (i) lateral contact/bed-perpendicular fronts; (ii) vertical contact/bed-parallel fronts; and (iii) complex-shaped fronts at the distal part of dolostone bodies. This morphological information, when coupled with detailed petrography, mineralogical and geochemical data could help to accurately reveal the governing processes behind the termination of dolostone bodies and their corresponding reaction front geometries. Our review shows that the first front type is primarily controlled by the interplay between intrinsic properties of the host rocks, dolomitizing fluids, and self-organization process. In contrast, the second front type is governed by the presence of laterally continuous depositional, diagenetic, or structural fluid barriers, creating a significant permeability contrast across beds. The formation of complex-shaped fronts is interpreted to be controlled by a combination of original lithological composition and kinetics. This overview provides the first multi-study categorisation of ancient dolomitization fronts and the controls on their formation at a range of scales. This improves our understanding of low temperature metasomatic processes, and their termination, in sedimentary systems. Furthermore, it highlights how accurate interpretation of the origin and styles of dolomitization fronts can improve our understanding of dolomitization processes, paleofluid flow, and distribution of economic resources in dolomitized carbonate platforms, which can be challenging to determine from the dolostone bodies themselves, where they have undergone multiple phases of recrystallization and diagenetic overprinting.
Keywords: dolostone; geobodies; fault/fracture; high-temperature; reaction front; hydrothermal